1990
DOI: 10.1099/00222615-31-2-125
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of methicillin-resistant Staphylococcus aureus by biotyping, immunoblotting and restriction enzyme fragmentation patterns

Abstract: Summary.We have characterised 45 isolates of methicillin-resistant Staphylococcus aureus (MRSA) from Glasgow Royal Infirmary by means of simple biotyping, immunoblotting of exported proteins and restriction enzyme fragmentation patterns (REFP) of plasmid DNA. The strains were subdivided into four groups (A-D) on the basis of biotype. Immunoblotting and restriction enzyme fragmentation generated a number of unique patterns. Analysis of these patterns by means of Dice coefficients of similarity separated them in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 4 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…An association between nasal carriage of S. aureus and subsequent infections was also described in studies evaluating patients on continuous ambulatory peritoneal dialysis (CAPD) [23]. On the bases of typing methods Coia et al [7] found identical isolates from the site of infection and from carriage sites. These results showed that for patients on CAPD a S. aureus carriage is an important risk factor for development of S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…An association between nasal carriage of S. aureus and subsequent infections was also described in studies evaluating patients on continuous ambulatory peritoneal dialysis (CAPD) [23]. On the bases of typing methods Coia et al [7] found identical isolates from the site of infection and from carriage sites. These results showed that for patients on CAPD a S. aureus carriage is an important risk factor for development of S. aureus infections.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci were identified based on Gram reaction (Gram-positive cocci in clumps), catalase, coagulase (tube method using rabbit plasma) and DNase tests. Biotyping was based on the hydrolysis of urea, Tween 80 and pigmentation on Isosensitest agar (Coia et al, 1990). Pigmentation was classified as yellow (Y), cream (C) or white (W).…”
Section: Methodsmentioning
confidence: 99%
“…These ranges from a traditional method like phage typing (Williams and Rippon, 1952), biotyping (Coia et al, 1990), serotyping (Melo Cristino et al, 1986), to classical methods, which make use of molecular biological techniques (pulse field gel electrophoresis (PFGE) (Wielders et al, 2002), ribotyping (Wielders et al, 2002), restriction fragment analysis of plasmid) such as looking at differences in chromosome and extra-chromosomal element like plasmid. This study was aimed in assessing the value of the detection of rDNA polymorphisms in the genome of S. aureus as a typing system in studying the epidemiology of MRSA.…”
Section: Methicillin Resistant Staphylococcus Aureusmentioning
confidence: 99%